Levo-tetrahydropalmatine attenuates the acquisition of fentanyl-induced conditioned place preference and the changes in ERK and CREB phosphorylation expression in mice. (21st June 2021) - Du, Kaili; Wang, Zhuoyi; Zhang, Huimin; Zhang, Yaofang; Su, Hongliang; Wei, Zhiwen; Zhang, Chao; Yun, Keming; Cong, Bin
Highlights: Fentanyl induced conditioned place preference (CPP) in mice. L-THP attenuated the acquisition of fentanyl-induced CPP in mice. Fentanyl induced upregulation of p-ERK and p-CREB in Hip, NAc, and PFC of mice. L-THP decreased the upregulation of p-ERK and p-CREB in Hip, NAc, and PFC of mice. Abstract: Levo-tetrahydropalmatine (L-THP) is the main active ingredient of Corydalis and Stephania and is widely used for its sedative, analgesic, and neuroleptic effects. Though L-THP is an antagonist of dopamine receptors and has been proven to be effective in treating drug addiction, its effect on fentanyl-induced reward learning still remains unclear. This experiment was designed to investigate the effects of L-THP on fentanyl-induced rewarding behavior through conditioned place preference (CPP) in mice. Western blot assays were used to dissect the accompanying changes in the phosphorylation of extracellular signal-regulated kinase (ERK) and cAMP response element binding protein (CREB) in related brain regions, including the hippocampus (Hip), caudate putamen (CPu), prefrontal cortex (PFC), and nucleus accumbens (NAc), which may mediate the effects of L-THP on fentanyl-induced CPP. The results revealed that fentanyl could induce CPP in mice at doses of 0.025 mg/kg, 0.05 mg/kg, 0.1 mg/kg, and 0.2 mg/kg, and L-THP could attenuate the acquisition of fentany-induced CPP at a dose of 10.0 mg/kg. The levels of p-ERK and p-CREB of the saline+fentanyl group (0.05 mg/kg) increased significantly in the Hip, NAc, and PFC compared to the saline+saline group. Furthermore, L-THP (10.0 mg/kg) co-administered with fentanyl during conditioning prevented the enhanced phosphorylation of ERK and CREB in the Hip, NAc, and PFC. Our research revealed that L-THP could suppress the rewarding properties of fentanyl-induced CPP, the inhibitory effect may be related to the suppression of ERK and CREB phosphorylation in the Hip, NAc, and PFC of mice. Thus, L-THP may have therapeutic potential for fentanyl addiction.